The Relationship Between Working Period and Comfort of Personal Protective Equipment (PPE) With Compliance Behavior of Using PPE In Cut Area Workers PT. Cahaya Bintang Olympic - Zufra Inayah; Nabiella Rahayu Kurniasih; Hilda Aulia Saputri; Habibun Nabila Nur Mustaqimah; Elok Pramiswara Ristanti (Yayasan Literasi Sains Indonesia, 2025)
PT Cahaya Bintang Olympic is one of the furniture processing industries with a high risk of accidents and occupational illnesses, particularly in the cutting area. One safeguard for workplace safety and health is the company's requirement to utilize Personal Protective Equipment (PPE). The aim of this study is to determine and examine how workers' compliance with PPE use in the cutting area is impacted by their comfort level and length of service. 36 workers made up the sample for this cross-sectional study, which employed an analytical descriptive method. Compliance with PPE use is the dependent variable, whereas duration of service and comfort level with PPE use are the independent variables. Questionnaires and observation sheets were used to gather data, and the chi-square test was used for analysis. According to the findings, the majority of employees fell into the long tenure category (52.8%), felt at ease using personal protective equipment (72.2%), and cooperated with PPE use (83.3%). PPE comfort with compliance with PPE use (p = 0.000) and length of service are significantly correlated with compliance with PPE use (p = 0.005). To maintain the comfort level of PPE use, it is advised that businesses enhance PPE comfort through suitable testing and changes.